Potential of Biogas Technology in Vinnytsia Region - Тkachenko, S. Yо.; Stepanov, D. V.; Stepanova, N. D.; Vlasenko, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2020)
Methods of obtaining energy from biomass are analyzed. It is stated that biogas technologies will soon become a mandatory element of livestock, agro-processing, food and other enterprises. It has been established that the replacement of fossil fuels with renewable energy sources has economic, environmental and social benefits. The components of the complex effect of the biogas plant are analyzed. The analysis of statistical information is carried out and the dynamics of change of livestock in Vinnytsia region is estimated. Groups of factors influencing the intensity of biogas production and its quality are systematized, namely biological, physical, chemical and organizational-technological. The influence of different types of raw materials is analyzed, their rational ratio is indicated taking into account the increase of biogas yield, improvement of its quality, the criteria according to which raw materials for biogas plants should be selected are indicated. Attention is paid to the processes of joint fermentation of livestock waste with vegetable raw materials; the effects of increasing the yield of biogas during cofermentation are given. The model of annual potential of biogas technology is formulated, on the basis of which the annual potential of Vinnytsia region is developed. The livestock as of 01.05.2020, the volumes of sugar production from sugar beet and alcohol in 2019 are taken into account. The potential of biogas production from livestock waste, sugar and alcohol production has been established. The energy effect of biogas technology, which includes the production of high-calorie energy, heat and electricity during its utilization, is determined. The energy potential of biogas technology is sufficient to cover the heat and electricity needs of Vinnytsia region for the main types of economic activity. The economically feasible potential has been determined according to the recommendations of the Bioenergy Association of Ukraine. Technological solutions to increase the efficiency of the biogas plant are proposed, namely the return to the technological process of the biogas plant liquid phase (fraction) in the amount of 10… 50 % of the obtained from the spent substrate, which saves up to 70 % of fresh water at stationary loading intervals bioreactor. A method for determining the complex effect of biogas technology based on the calculation of the energy effect and taking into account expert assessments of the ratio of energy, economic and environmental and social effects is proposed. It is indicated that this method of estimating the complex effect allows drawing a conclusion about the expediency of conducting a detailed technical and economic analysis of the future biogas plant under specific conditions.